Marketing Performance and Marketing Sustainability In Msmes In Pekanbaru City: Innovation Capability, Market Orientation And Branding - Wijayanto, Gatot; Jushermi, Jushermi; Nursanti, Aida; Pramadewi, Arwinence; Novandalina, Arini; Rivai, Yutiandry (Indonesian Scientific Publication, 2024)
In the dynamic setting of Pekanbaru City, this study explores the complex interactions among innovation capacity, market orientation, and branding, and their effects on marketing performance and sustainability in Micro, Small, and Medium-Sized Enterprises (MSMEs). Structural Equation Modeling (SEM-PLS 4) was utilized for investigation in a quantitative method with 215 respondents. The study reveals important positive correlations between marketing performance and innovation ability, market orientation and marketing sustainability, and marketing performance and sustainability enhanced by successful branding. Additionally, the synergistic relationship among branding, market orientation, and innovation affects marketing results and sustainability. These findings have important ramifications for MSMEs, policymakers, and researchers. They offer practical guidance for improving tactics and promoting sustainability in the MSME sector of Pekanbaru City.